On-field assessment of concussion: clinical utility of the King-Devick test - Legarreta, Andrew D (Open Access J Sports Med, 2019)
Sport-related concussion (SRC) is an important public health concern with up to 3.8 million SRCs occurring each year. As the incidence and rate of SRC increases, reliable and valid tools for diagnosis and management are needed. The King-Devick (K-D) test assesses a patient’s visual function based on reading a series of numbers as well as counting both time to completion and errors. Its rapid administration time and simplicity make the K-D test a potentially useful SRC diagnostic tool, though limitations exist in baseline testing and what constitutes an abnormal score. Additionally, the K-D tests should never be used in isolation to diagnose a concussion, but rather as one test in conjunction with additional clinical measures, as part of an individualized approach to each patient. The current review examines the clinical utility of the K-D test.